Perceived Barriers to Following Dietary Recommendations in Hypertensive Patients. (3rd April 2017) - Mahdavi, Reza; Bagheri asl, Azadeh; Abadi, Mohammad Asghari Jafar; Namazi, Nazli
ABSTRACT: Objective : Hypertension (HTN) is one of the most important public health problems in the world. Lifestyle modification including dietary changes such as following the Dietary to Stop Hypertension (DASH) plan is the first step to control HTN. The aim of the present study was to identify perceived barriers to following dietary recommendations in hypertensive patients in Zanjan, Iran. Materials and Methods : In this cross-sectional study, 200 outpatients (161 women, 39 men) with essential HTN (systolic blood pressure [SBP] ≥ 140 mmHg and diastolic blood pressure [DBP] ≥ 90 mmHg) were recruited from August to November 2012. A 29-item structured questionnaire was designed to assess perceived barriers to follow dietary recommendations. Validity and reliability were assessed by content validity index, content validity ratio, and Chronbach's alpha, respectively. An exploratory factor analysis with a principal component analysis extraction method and varimax rotation was performed to extract the underlying factors. Results : Mean age and body mass index (BMI) of participants were 46.9 ± 5.5 years and 30.6 ± 3.6 kg/m 2, respectively. The exploratory factor analysis extracted 6 interpretable factors with eigenvalue > 1. In order of importance, they were social and environmental barriers (eigenvalue = 2.489), social gathering (eigenvalue = 2.379), compliance with recommended diet and preference of other family members (eigenvalue = 2.127), palatability of the recommended diet (eigenvalue = 1.972), emotional statues and psychological factors (eigenvalue = 1.921), and cost (eigenvalue = 1.845). Mentioned factors explained 44% of the total variance. Conclusion : Patients with HTN in our study perceived some barriers to following the recommended diet. In nutritional counseling, considering these barriers may be effective in improving the dietary adherence level in hypertensive patients.